An Assessment of the Determinants of Productivity in the Electricity Industry in Nigeria - David, Olatunji, Olabode (European Scientific Journal, ESJ, 2018)
The study examined the productivity in the electricity industry in Nigeria. The aim of the study was to ascertain the determinants of productivity in the electricity sector. The research design adopted for the study was a longitudinal study of productivity in the electricity industry in Nigeria. The study considered time series data for a 20 year period from 1996 to 2015. Data on study variables were obtained from Central Bank of Nigeria (CBN) statistical bulletins, National Bureau of Statistics (NBS) annual publications, and the websites of both Transparency International (TI) and Energy Information Administration (EIA). Based on the study objectives, the fully modified ordinary least square (FM-OLS) technique was used to estimate the multiple regressions between productivity and the explanatory variables. Data analyses were carried out using the software application of E- View 9.0. Results from the study showed that the total factor productivity which is an indication of efficiency in the electricity sector was 0.29. This is low when compared with international best practice of 0.80. Also, results from the study revealed that funding, weather condition, vandalism and labour supply have significant effect on productivity of the electricity industry in Nigeria. However, tariff structure and corruption were not statistically significant in the prediction of productivity in the electricity industry. The study recommended that increased budgetary allocations should be made available to the electricity industry to provide the needed improvements in the sector.